Emicizumab: a novel drug in hemophilia A prophylaxis – a narrative review. Issue 10 (3rd October 2022) - Mazurkiewicz, Łukasz; Czernikiewicz, Krystian; Rupa-Matysek, Joanna; Gil, Lidia
ABSTRACT: Introduction: Hemophilia A is a genetically conditioned disease leading to hemostatic disorders due to factor VIII (FVIII) deficiency. The treatment of hemophilia has evolved throughout the past years and has significantly changed. One of the newest drugs for prophylactic treatment is the humanized bispecific IgG antibody – emicizumab, which binds with factor IXa and factor X, bridging those factors and thus mimicking the activity of factor VIII. Areas covered: The literature search was done via the PubMed database, with the emphasis on clinical trials and case reports, describing the off-label emicizumab use. This review presents an extensive summary and considers the advantages and disadvantages (side-effects) of emicizumab, describing additional clinical situations, where emicizumab has been successfully used. In our review, we cover information about the mechanisms of action, indications, and efficacy and discuss some chosen case reports about off-label emicizumab use. Expert Opinion: Its convenient administration method (subcutaneous) and frequency of injections (from once a week to once a month) makes it a more comfortable treatment, limiting injection–site reactions, hospital stays, costs of prophylaxis, and significantly increasing patients' quality of life. Adverse effects are scarce and rarely serious – the most common ones are reactions at the injection-site and upper respiratory tract infections.